Slow Moving Capital - Mitchell, Mark; Pedersen, Lasse Heje; Pulvino, Todd (American Economic Review, 2007)
We study three cases in which specialized arbitrageurs lost significant amounts of capital and, as a result, became liquidity demanders rather than providers. The effects on security markets were large and persistent: Prices dropped relative to fundamentals and the rebound took months. While multi-strategy hedge funds who were not capital constrained increased their positions, a large fraction of these funds actually acted as net sellers consistent with the view that information barriers within a firm (not just relative to outside investors) can lead to capital constraints for trading desks with mark-to-market losses. Our findings suggest that real world frictions impede arbitrage capital.